Sequestration of carbon dioxide (CO2) using bio-foamed concrete brick incorporating bacillus tequilensis bacteria - Abdulaziz Al-Shalif, Abdullah Faisal (2020)
The emission of carbon dioxide (CO2) into the atmosphere increased rapidly in the last decades, which lead to global warming, climate change and rise in sea level. This research aimed to contribute on sequestration of CO2 using biological approach to sequestrate CO2 in bio-foamed concrete bricks (B-FCB). The used of biological approach in B-FCB is considered as new direction of CO2 sequestration which in role helps to reduce the amount of CO2 from atmospheric at the same time improve the strength and physical properties of B-FCB via precipitation of calcium carbonate (CaCO3). The Bacillus tequilensis successfully isolated from cement kiln dust (CKD) to acclimatize in B-FCB. The B.tequilensis have the ability to produce carbonic anhydrase (CA) and urease enzymes to sequestrate CO2 and convert it to CaCO3. 2k factorial and Response Surface Method (RSM) analysis were used to optimise carbonation depth and compressive strength of B-FCB using four factors, density (D), B.tequilensis (B), temperature (T) and CO2. By given priority to carbonation depth the optimal carbonation depth and compressive strength of B-FCB used were 9.3 mm and 3.3 MPa at the following conditions; 20 % of CO2, 3x105 of B, 40 ºC of T and 1550 kg/m3 of D at 28 days. The use of B in B-FCB increase CO2 uptake by 29.7 % compared to foamed concrete brick without B.tequilensis (FCB) at 28 days. In addition, the use of B in B-FCB improve compressive strength, reduce initial rate of water absorption, water absorption and increase carbonation depth via 35.5 %, 76.4 %, 20.2 % and 30.0 % compared to FCB respectively. The change in chemical elements levels and increasing crystallinity precipitation in the form of CaCO3 were analysed by SEM, EDX and XRD. Microstructure analysis confirmed the improvement of the compressive strength and physical properties of B-FCB compared to FCB, which was analysed via SEM, EDX and XRD.